PENGARUH NET PROFIT MARGIN, CURRENT RATIO, DEBT TO ASSET RATIO DAN TINGKAT SUKU BUNGA TERHADAP BETA SAHAM SYARIAH PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Julduha, Nucifera; Kusumawardhani, Indra (Buletin Studi Ekonomi; VOL.18.NO.2.AGUSTUS 2013. (PP 85-190), 2014)
Abstract : The Effect of Net Profit margin, Current Ratio, Debt to Asset ratio and Interest Rate of Syariah Beta Stock in The Company That Listed in Jakarta Islamic Index. The aim of this study is to examine whether Net Profit Margin, Current Ratio, Debt to Asset Ratio, and the Interest Rate affect Syariah Stock Beta on the companies listed in Jakarta Islamic Index during 2009-2011. 45 samples were obtained with purposive sampling. Results show that Net Profit Margin, Current Ratio, Debt to Asset Ratio, and the Interest Rate simultaneously affect Syariah Stock Beta, while only net Profit Margin partially affected Syariah Stock Beta.
Keywords: Net Profit Margin, Current Ratio, Debt to Asset Ratio, Interest Rate, Syariah Stock Beta